2006
DOI: 10.1021/la0618972
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Molecular Order in Poly(3-alkylthiophene) Thin Films with Polarizing Spectroscopies

Abstract: We measured the molecular order of poly(3-alkylthiophene) chains in thin films before and after melting through the combination of several polarized photon spectroscopies: infrared (IR) absorption, variable angle spectroscopic ellipsometry (SE), and near-edge X-ray absorption fine structure (NEXAFS). The data from the various techniques can be uniformly treated in the context of the dielectric constant tensor epsilon for the film. The combined spectroscopies allow determination of the orientation distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
246
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(268 citation statements)
references
References 42 publications
17
246
3
2
Order By: Relevance
“…In the 'molecular schematic' , the alkyl chains are not explicitly drawn because there is no evidence based on the diffraction or Fourier transform infrared spectroscopy (FTIR) (Supplementary Fig. S1) of chain crystallinity, and because the chains are not confined to a single layer owing to the high density of gauche defects 21,22 . Figure 4c shows that the undulations between neighbouring bilayers are out-of-phase with each other and this allows the alkyl chains to aggregate giving the appearance of a chain of alkyl beads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 'molecular schematic' , the alkyl chains are not explicitly drawn because there is no evidence based on the diffraction or Fourier transform infrared spectroscopy (FTIR) (Supplementary Fig. S1) of chain crystallinity, and because the chains are not confined to a single layer owing to the high density of gauche defects 21,22 . Figure 4c shows that the undulations between neighbouring bilayers are out-of-phase with each other and this allows the alkyl chains to aggregate giving the appearance of a chain of alkyl beads.…”
Section: Resultsmentioning
confidence: 99%
“…Gilbert for the software package IGOR Pro 6 (Wavemetrics) 30 . To determine the exact peak positions of each vibrational mode, we modelled the observed spectra with a combination of six Lorentzians 21 . Most relevant to this work was the peak position of the methylene anti-symmetric stretch at 2,928 cm − 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that this results in a lamellar structure formed by interchain stacking ( Figure 5). It has also been shown that the hole mobility varies by two orders of magnitude depending on orientation (parallel or normal to the substrate) of the lamellae [53,54,[81][82][83][84][85][86], the normal one giving the highest mobility. …”
Section: Poly(3-hexylthiophene) (P3ht)mentioning
confidence: 99%
“…It has been shown that this results in a lamellar structure formed by interchain stacking ( Figure 5). It has also been shown that the hole mobility varies by two orders of magnitude depending on orientation (parallel or normal to the substrate) of the lamellae [53,54,[81][82][83][84][85][86], the normal one giving the highest mobility. According to the work of Alberga et al [53], spin-coated then annealed P3HT displays three different zones: an interfacial zone close to the substrate (thickness of 10 Å), an intermediate zone 30 Å thick atop and an OSC/electrolyte interfacial zone over this distance; the first layers display the highest degree of order [53,[87][88][89].…”
Section: Poly(3-hexylthiophene) (P3ht)mentioning
confidence: 99%
“…4(a), a detailed analysis of the anisotropic optical constants can further reveal morphological details. 51,52,53 The optical constants n xy and k xy describe light-polymer interaction for polymers with their c axes aligned parallel to the substrate surface, while the z-component describes upright polymers with their c axes oriented in z-direction, Fig. 4(b).…”
Section: Polymersmentioning
confidence: 99%